The adverse effect of energy-efficiency policy - Achim Voß (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
I analyze energy-efficiency policy as a prescription of a minimum-efficiency standard for energy-using household goods like cars, building insulation, and home appliances. Such a policy has two effects. At the intensive margin, a household that invests will choose a more efficient device. At the extensive margin, there will be more households that choose not to invest at all. Thus, additional to and different from rebound effects, energy-efficiency policy may have unintended consequences. I analyze the equilibrium effects of a minimum-efficiency standard, taking price adjustments and household heterogeneity into account. A moderate minimum-efficiency standard increases demand for efficiency-enhancing household capital goods, and reduces energy demand. More stringent policy is shown to be less effective or even counterproductive. For the case of a fixed supply of efficiency-enhancing capital, it is shown that minimum-efficiency standards increase equilibrium energy demand. Finally, I analyze which households benefit from minimum-efficiency standards and which ones lose. A standard induces investing households to expend more for household capital and less for energy. The wedge between the induced expenditures and the private optimum is analyzed as a deadweight loss.
Keywords: Q41; Q48; D15; 330; Energy Efficiency; Rebound Effects; Household Heterogeneity; Extensive Margin; Gruenspecht Effect; Investment; Theory of Environmental Policy